American idol: evidence of same-race preferences? - Jungmin Lee (Institute for the Study of Labor (IZA), 2006)
This study examines whether viewers of the popular television show, American Idol, are racially biased. I find strong evidence for same-race preferences, in particular among black viewers. Featuring more black contestants attracts more black households to tune in to watch the show. And, with more black viewers, a black contestant is less likely to be voted off.
Keywords: J15; L82; 330; customer discrimination; TV viewership; voting